Development of an enzymatic method for quantification of dichlorvos from environmental samples - Ganguru, Uma Maheswara Rao; Yalavarthy, Prameela Devi (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> A simple, low cost and sensitive novel enzymatic tablet method was developed for the quantification of an organophosphorus pesticide, dichlorvos (2,2-dimethyl dichlorovinyl phosphate) at microgram level. The method involves in quantification of dichlorvos is based on inhibition of the enzyme, Succinate Dehydrogenase (SDH) (EC.No. 1.3.5.1). The substrate, sodium succine specifically binds to the enzyme (SDH) and develops color in the presence of chromogenic reagent. This chromogenic reagent contains INT (2-(4- Ido-phenyl)-3-(4-nitrophenyl)-5 phenyl tetrazolium chloride) and PMS (N-methyl phenazonium methosulphate). Lyophilized egg albumin powder was used as a source of SDH enzyme. Two tablets, one containing the enzyme and the other containing a mixture of substrate and chromogenic agent were prepared. Optimization of the tablet method was done by standardizing the conditions for colorimetric analysis: optimum pH (7), optimum temperature (80ºC), enzyme concentration (lyophilized egg albumin powder) (10mg/tablet) and optimum reaction incubation time (30 min). Percentage of enzyme inhibition and concentration of dichlorvos at a range of 0-65 µg was plotted, which was observed to follow the Beer Lambert’s Law. A color chart was prepared for quantification of dichlorvos based on the formation of formazan in the reaction. If the concentration of environmental samples is within the given range, the samples can be quantified by comparing with the color chart. The method is successfully applied for quantification of dichlorvos from environmental samples.